2021
DOI: 10.1108/jbim-01-2020-0017
|View full text |Cite
|
Sign up to set email alerts
|

Value co-creation: a review of literature and future research agenda

Abstract: Purpose The purpose of this paper is to present a systematic review of the available literature on value co-creation (VCC) and provide insightful future directions for research in this domain. Design/methodology/approach The extant literature on VCC has been reviewed by collecting relevant research papers based on certain specified delimiting criteria. A total of 110 research papers have been analysed to gain useful insights into VCC literature. Findings The study analyses the literature on VCC and provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 96 publications
(123 reference statements)
2
45
0
3
Order By: Relevance
“…Before adopting technology, individuals tend to calculate the benefits which they will receive and how many resources they must spend to avail themselves of those benefits (Jebarajakirthy et al, 2020;Shankar and Jain, 2021). The literature suggested that perceived values play a crucial role in framing individual behavioural intention (Hsieh and Lin, 2018;Jebarajakirthy and Shankar, 2021;Saha et al, 2021). Similarly, in the context of HRMS, employees tend to calculate how new technology will provide different functional, hedonic and social values, and how much they have to spend to receive those benefits (Zhang et al, 2017;Shankar and Yadav, 2020).…”
Section: Perceived Valuementioning
confidence: 99%
“…Before adopting technology, individuals tend to calculate the benefits which they will receive and how many resources they must spend to avail themselves of those benefits (Jebarajakirthy et al, 2020;Shankar and Jain, 2021). The literature suggested that perceived values play a crucial role in framing individual behavioural intention (Hsieh and Lin, 2018;Jebarajakirthy and Shankar, 2021;Saha et al, 2021). Similarly, in the context of HRMS, employees tend to calculate how new technology will provide different functional, hedonic and social values, and how much they have to spend to receive those benefits (Zhang et al, 2017;Shankar and Yadav, 2020).…”
Section: Perceived Valuementioning
confidence: 99%
“…We retrieved 512 articles from our article search process and adhered to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines (Moher et al, 2015) for articles' inclusion/exclusion process. Accordingly, at the first stage, we identified and excluded 217 duplicates: articles downloaded more than once from online databases (Saha et al, 2022). We then employed eligibility criteria to shortlist the suitable articles for our study.…”
Section: Methodsmentioning
confidence: 99%
“…An Air France food truck cruised down the streets of Manhattan a few years ago, handing out free samples of inflight meals to the public (Meece, 2011). Hence, it can be stated that full-service carriers prioritize “customer retention” by building and maintaining customer loyalty, the key to its success in the long run (Saha et al. , 2021; Carlos Martín et al.…”
Section: Literature Reviewmentioning
confidence: 99%